Development of Financial Literacy Learning Modules Based on Mutual Cooperation in Elementary Schools Class V - Muhamad Wildan Solihin; Endang Herawan; Auliya Aenul Hayati (Journal of Educational Sciences, 2026)
This study was motivated by the limited availability of contextual financial literacy, instructional materials and the inadequate integration of gotong royong values within the learning process. The objective of this study was to develop and evaluate a gotong royong-based financial literacy module for fifth-grade elementary school students. The method employed was the ADDIE model with a limited trial involving 19 fifth-grade students at a single elementary school. Data were collected through needs questionnaires, expert validation, learning outcome tests, and student worksheet observations. The results demonstrated an average validity score of 3.87 (96.75%, highly valid), student practicality of 98.42% (highly practical) and teacher practicality of 80.00% (practical), and effectiveness indicated by score improvement from 82.6 to 93.7 with a classical mastery rate of 95%. This module contributes as appropriate and contextual instructional material integrating cognitive and social aspects. It is recommended to be tested on a broader scale to enhance generalization and context adaptation.